Adsorption of serum protein in chitosan-coated and polyethyleneimine-coated magnetite nanoparticles - Chapa, Christian (2021)
Magnetite (Fe3O4) nanoparticles provide several possibilities for a compelling platform for medical applications due to their magnetic properties. In the same way, functionalization with polymers provides several properties seeking to achieve colloidal stabilization in physiological fluids. Nonetheless, the use of magnetite nanoparticles as a medical agent is still in its early stages and is faced with many doubts and challenges as the study of coatings interactions with biological molecules. In this work, Fe3O4 nanoparticles were synthetized by co-precipitation method and further coated with chitosan, as well as coated with polyethyleneimine. The nanoscale size of magnetite nanoparticles was confirmed using scanning electron microscopy. Fourier-transform infrared spectroscopy corroborated that characteristic functional groups of chitosan and polyethylenimine were present in the surface modified magnetite samples. The evaluation of protein immobilization was carried out by incubating bovine serum albumin at different concentrations followed by magnetic decantation using a permanent magnet. Coated magnetite nanoparticles have a protein absorption greater than bare MNP